PENGARUH MOTIVASI, CITRA PERUSAHAAN DAN KEPERCAYAAN TERHADAP NIAT BERTRANSAKSI ULANG - Citra Riyanto, 09.05.51.0027 (Students Journal of Economic and Management, 2014)
This study aimed to analyze the influence of Motivation, Corparate Image and Intention Trunst in Transaction Brithday in customer intention to Koperasi transaction. This behavior does not only happen to certain customers but all customers that there koperasi.Samples taken are all consumers business comperative âesgeefâ Commercial Markets Peterongan Semarang region that has been conducting transaction whithim the last 2 years, amounting to 100 people repsonden.Based on the analysis using the t test is conclude Motivation variable t test value of 0.543 whit 0.000 sig, sig t test (<) 0.005 so it can be concuded the motivation variable positive ang significant effect on Intetion Transaction Birthday. Variable t test value of 0.340 with Corporate Image sig sig 0.000 t test (<) 0.005 so it can be concluded that the Corporate Image variable positive and significant effect on Intention Transaction Birthday. t test value of 0.143 with a confidance sig 0.143 t test (<) 0.005 so it can be concluded that the Trust variable positive and significant effect on Intention Transaction Birthday.